The Effect of Sugar Concentration and Citric Acid on Physicochemical Characteristics of the Pumpkins Syrup (Cucurbita moschata Durch) - Haloho, Megawati; Handoko, Yoga A (Universitas Pattimura, 2023)
Pumpkins (Cucurbita moschata Durch) are a food commodity with very high nutritional content, abundant production, and affordable prices, but their utilization has not been maximized. The syrup is a processed product made from sugar and water, with a minimum sugar moisture content requirement of 65%. The syrup is made from yellow pumpkins with food additives such as sugar, carboxyl methyl cellulose, citric acid, and lime. Variations in concentrations of sugars between 65% and 70% and citric acid between 0%, 0.1%, 0.3%, and 0.5%, are expected to affect pH, total dissolved solids, reduction sugars, vitamin C, and beta-carotene. The research objective was to study and determine the effects of cane sugar and citric acid concentrations on pumpkin syrup's physical, chemical, and organoleptic properties. pH, total dissolved solids, reducing sugars, vitamin C, and beta-carotene content were measured using a pH meter, a hand refractometer, the Nelson-Somogyi method, the iodometric method, and the spectrophotometer method, respectively, and organoleptic properties were evaluated using the sensory test. Results showed that variations in the addition of sugar and citric acid had a pH of 3.46-6.00, total dissolved solids 10.33-11.4 (obrix); reduction sugars of 19.4%-30.21%, vitamin C of 20.53-38.13 (mg/100 g); and beta-carotene of 1.24-2.82 mg/100 g. Pumpkin syrup made by adding 65% sugar and 0.5% citric acid (A1B3) was found to have the best concentration and was liked by panelists for its aroma, color, and taste.